TiCr alloy anodization for Cr-doped TiO2 nanotube array with improved photocatalytic activity. (5th April 2019) - Xue, Chaorui; Hu, Shengliang; Chang, Qing; Li, Ying; Li, Ning; Li, Chengzhen; Yang, Jinlong
Abstract: Cr-doped anodic TiO2 nanotube array has been prepared with increased photocurrent compared to pristine titania. However, detailed effect of Cr-addition in titanium on the growth and photocatalytic property of anodic nanotube is still indistinct. To clarify this point, we initially compared the morphology, crystallinity and chemical composition of anodic nanotube arrays on various TiCr alloys. The results indicated that tube length and diameter were increased by TiCr alloy anodization, and Cr atoms were doped inside TiO2 in the form of Cr 2+, Cr 4+ and Cr2 O3 . Because of Cr-doping, anatase crystallization of nanotube was inhibited. The photocatalytic activities were next evaluated. Compared to pristine Ti, Ti0.2Cr and Ti0.5Cr, Ti0.1Cr anodization was found to be optimum for preparing nanotube array with improved photocatalytic activity. The reason could be the improved UV-visible light absorption and photo-generated carriers utilization efficiency due to appropriate Cr doping. For Ti0.2Cr and Ti0.5Cr anodization, excess Cr2 O3 could be formed, cause the recombination of photo-generated carriers, and reduce the photocatalytic property. The results presented in this work may offer useful guidelines for Ti alloy anodization towards preparation of nanostructured photocatalysts with promising applications.